2020
DOI: 10.1093/qje/qjaa008
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Centric Model of Demand Recessions and Speculation*

Abstract: We provide a continuous-time “risk-centric” representation of the New Keynesian model, which we use to analyze the interactions between asset prices, financial speculation, and macroeconomic outcomes when output is determined by aggregate demand. In principle, interest rate policy is highly effective in dealing with shocks to asset valuations. However, in practice monetary policy faces a wide range of constraints. If these constraints are severe, a decline in risky asset valuations generates a demand recession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…We also contribute to a macro-finance literature that has debated the tradeoffs between behavioral and rational modeling approaches, with survey evidence providing an important input (see Cochrane, 2011Cochrane, , 2017Greenwood and Shleifer, 2014;Adam, Matveev and Nagel, 2018). Among the many proposed equilibrium models, the most relevant for our work are those that directly incorporate survey evidence (e.g., Barberis et al, 2015;Adam, Marcet and Beutel, 2017;Bhandari, Borovička and Ho, 2016) and those that feature heterogeneous belief (e.g., Scheinkman and Xiong, 2003;Geanakoplos, 2010;Caballero and Simsek, 2017;Martin and Papadimitriou, 2019).…”
mentioning
confidence: 99%
“…We also contribute to a macro-finance literature that has debated the tradeoffs between behavioral and rational modeling approaches, with survey evidence providing an important input (see Cochrane, 2011Cochrane, , 2017Greenwood and Shleifer, 2014;Adam, Matveev and Nagel, 2018). Among the many proposed equilibrium models, the most relevant for our work are those that directly incorporate survey evidence (e.g., Barberis et al, 2015;Adam, Marcet and Beutel, 2017;Bhandari, Borovička and Ho, 2016) and those that feature heterogeneous belief (e.g., Scheinkman and Xiong, 2003;Geanakoplos, 2010;Caballero and Simsek, 2017;Martin and Papadimitriou, 2019).…”
mentioning
confidence: 99%
“…Brunnermeier and Sannikov (2014) and He and Krishnamurthy (2012), ,2013), ,2019a) demonstrate the ability of globally solved nonlinear continuous‐time models to explain financial crises and to evaluate policies that target financial stability. Caballero and Simsek (2020), ,2019) extend these tools so that they are tractable enough for use in analytical models. Additional work in this field include Adrian and Boyarchenko (2012), Maggiori (2017), Di Tella (2017), and Van der Ghote (2019).…”
Section: Related Literaturementioning
confidence: 99%
“…Therefore, the cycle of house prices and consumption growth is closely synchronized (Aoki et al, 2004;Attanasio et al, 2005;Katagiri, 2018). However, high house prices are often tied to financial systemic risk (Caballero & Simsek, 2020). In the cycle of rising house prices, there are asset bubbles, bloats, and bursts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the research of the dynamic stochastic general equilibrium model, it has been found that the macroprudential policy and monetary policy implemented by the Central Bank can effectively improve the welfare level of citizens when the negative impact occurs in the economy (Caballero & Simsek, 2020). The level of welfare depends on the level of household consumption.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%